Pengaruh Rebusan Daun Salam Terhadap Penurunan Tekanan Darah pada Pasien Hipertensi Di Puskesmas Baluase - Jumain; Wahyu; Agustinus Talindong; Irzan; Parmi; Sudirman (Universitas Widya Nusantara, 2025)
According to the World Health Organization (WHO), 1.28 billion adults worldwide will suffer from hypertension by 2023. 46% of people with hypertension are affected across various regions. Africa has the highest prevalence of hypertension at 27%, while the Americas have the lowest prevalence at 18%. Based on interviews with four people in Baluase Village, one person stated they already knew that boiled bay leaves could lower high blood pressure, while three hypertensive patients stated they were unaware that boiled bay leaves could lower blood pressure. The purpose of this study was to determine the effect of boiled bay leaves on lowering blood pressure in hypertensive respondents in Baluase Village, within the Baluase Community Health Center (Puskesmas) working area. This study was quantitative, with a pre-experimental design with a one-group pre-test-post-test design. The data types used were primary and secondary data. Data analysis used univariate and bivariate analysis. The population in this study amounted to 26 people. The sample in this study amounted to 26 respondents, the sampling technique used total sampling. The results of the study showed that the results of the Wilcoxon test obtained showed that there was an effect of bay leaf decoction on reducing blood pressure in hypertensive respondents with a p value = 0.000 (p <0.05), the pre-test results were 53.8% with level 1 hypertension, and the post-test results were 88.5% with pre-hypertension. The conclusion of this study is that there is an effect of bay leaf decoction on reducing blood pressure in hypertensive respondents in Baluase Village, Baluase Health Center Working Area. Suggestions It is hoped that this study can be a comparison and reference for further research. For health workers at the Baluase Health Center, it is hoped that they can apply traditional medicine for hypertension sufferers.